Analisis Yuridis Terhadap Rekam Medis Elektronik Sebagai Alat Bukti Sengketa Medis - Razak, Kaisar (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The development of information technology in the health sector has changed the paradigm of medical record management from a conventional system to an electronic one. Electronic Medical Records (RMEs) are now an important instrument in medical practice as well as potentially as evidence in medical disputes. This study aims to analyze the legal position of electronic medical records as evidence in medical dispute resolution from the perspective of positive Indonesian law. The research uses normative juridical methods with legislative and conceptual approaches, analyzing related regulations and judicial practices. RME has legal force as an electronic evidence under the ITE Law, but faces challenges related to authenticity, data integrity, and system standardization. Regulatory harmonization and strengthening of technological infrastructure are needed to optimize the role of RME as a valid and reliable evidence in medical disputes